The ActA protein of Listeria monocytogenes acts as a nucleator inducing reorganization of the actin cytoskeleton. - Pistor, S (1994)
Listeria monocytogenes, a facultative intracellular pathogen, employs actin and other microfilament-associated proteins to move through the host cell cytoplasm. Isogenic mutants of L. monocytogenes lacking the surface-bound ActA polypeptide no longer interact with cytoskeletal elements and are, as a consequence, non-motile (Domann et al., 1992, EMBO J., 11, 1981-1990; Kocks et al., 1992, Cell, 68, 521-531). To investigate the interaction of ActA with the microfilament system in the absence of other bacterial factors, the listerial actA gene was expressed in eukaryotic cells. Immunofluorescence studies revealed that the complete ActA, including its C-terminally located bacterial membrane anchor, colocalized with mitochondria in transfected cells. When targeted to mitochondria, the ActA polypeptide recruited actin and alpha-actinin to these cellular organelles with concomitant reorganization of the microfilament system. Removal of the internal proline-rich repeat region of ActA completely abrogated interaction with cytoskeletal components. Our results identify the ActA polypeptide as a nucleator of the actin cytoskeleton and provide the first insights into the molecular nature of such controlling elements in microfilament organization.